2005
DOI: 10.1002/hep.20658
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of hepatopulmonary syndrome: Impact of liver transplantation

Abstract: H epatopulmonary syndrome (HPS) is a pulmonary vascular disorder characterized by the clinical triad of chronic liver disease, intrapulmonary vascular dilatations, and arterial hypoxemia. 1,2 Portal hypertension (with or without cirrhosis) is often present. 2,3 The intrapulmonary vascular dilatations are identified by transthoracic contrast echocardiography (qualitative) or radionuclide lung perfusion scanning with brain uptake to measure shunt fraction (quantitative). 2 The degree of arterial hypoxemia associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
392
8
21

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 407 publications
(438 citation statements)
references
References 20 publications
14
392
8
21
Order By: Relevance
“…HPS is defined as the presence of liver disease and/or PH and intrapulmonary vascular dilatation, resulting in an abnormal age-corrected alveolar-arterial oxygen gradient (partial pressure of oxygen [PaO2] of b80 mmHg, and an AaPO2 of N15 mmHg, or N20 mmHg in patients N64 years of age) [58]. A taxonomy of the severity of the HPS based on alterations in oxygenation is essential because severity influences survival and is useful in determining the timing and the risks of orthotopic liver transplantation (OLT) [59,60]. The pulmonary gas exchange abnormalities of HPS are characterized by hyperventilation and arterial deoxygenation that can be mild (PaO2 b 80 mmHg), moderate (PaO2 b70 mmHg), or severe (PaO2 b 60 mmHg) [58].…”
Section: Pulmonary Complications 261 Hepatopulmonary Syndromementioning
confidence: 99%
“…HPS is defined as the presence of liver disease and/or PH and intrapulmonary vascular dilatation, resulting in an abnormal age-corrected alveolar-arterial oxygen gradient (partial pressure of oxygen [PaO2] of b80 mmHg, and an AaPO2 of N15 mmHg, or N20 mmHg in patients N64 years of age) [58]. A taxonomy of the severity of the HPS based on alterations in oxygenation is essential because severity influences survival and is useful in determining the timing and the risks of orthotopic liver transplantation (OLT) [59,60]. The pulmonary gas exchange abnormalities of HPS are characterized by hyperventilation and arterial deoxygenation that can be mild (PaO2 b 80 mmHg), moderate (PaO2 b70 mmHg), or severe (PaO2 b 60 mmHg) [58].…”
Section: Pulmonary Complications 261 Hepatopulmonary Syndromementioning
confidence: 99%
“…Pharmacological agents have not proven to be uniformly beneficial in HPS, and liver transplantation (LT) is currently the only effective treatment option available for these patients. [3][4][5] POPH, on the other hand, involves elevated pulmonary artery (PA) pressures (mean, MPAP) and increased PVR, as measured by right heart catheterization (RHC), because of generalized pulmonary arterial vasoconstriction and proliferative vasculopathy, with microthrombi, vascular remodeling, and plexiform changes. Symptoms include dyspnea, along with signs of right heart failure.…”
mentioning
confidence: 99%
“…Along these lines, “extended‐criteria” allografts have been associated with increased graft dysfunction 51, and their use must be considered judiciously, on a case‐by‐case basis in HPS patients at high risk of developing severe posttransplant hypoxemia. However, given that the risk of severe posttransplant hypoxemia increases with the severity of baseline hypoxemia 10, and that hypoxemia is rapidly progressive in HPS 7, 9, this risk must be weighed against the benefit of reduced transplant wait times afforded by use of extended‐criteria organs. This is an area that requires further research.…”
Section: Other Considerationsmentioning
confidence: 99%
“…Although select, highly specialized centers have demonstrated good posttransplant outcomes in very severely hypoxemic patients with HPS 9, 52, in addition to the increased risk of posttransplant hypoxemia 10, studies have demonstrated increased overall posttransplant mortality in patients with a pretransplant PaO 2 ≤50 mmHg 7, 11, 53. These data, along with the expected decline in PaO 2 of 5.2–13.5 mmHg per year in patients with HPS 7, 9 coupled with expected delays to transplantation, form the basis for the UNOS MELD exception threshold of PaO 2 <60 mmHg in HPS. In centers with transplant waiting times that routinely result in a drop in PaO 2 to ≤50 mmHg by the time of transplant in these patients (despite allocation of MELD exception points), even more aggressive prioritization approaches may be required to reduce the incidence of this complication.…”
Section: Other Considerationsmentioning
confidence: 99%
See 1 more Smart Citation